ADICIONES AL CONOCIMIENTO DE PLIOLESTES TRIPOTAMICUS REIG, 1955 (MAMMALIA, MARSUPIALIA, CAENOLESTIDAE) DEL PLIOCENO SUPERIOR DE LA ARGENTINA. (Ameghiniana, 2013)
1) the type and a new specimen of Pliolestes tripotamicus Reig, 1955 (Marsupialia, Caenolestinae) from the upper Pliocene are respectively reanalyzed and described; 2) a new specirnen, provisionally assigned to Pliolestes sp. from the lower Pliocene (Chasicoan age) is described; 3) as a consequence, a revised diagnosis of Pliolestes is proposed. Regarding the relationship between the Caenolestidae and the Polydolopidae (Caenolestoidea) the following are discussed: 1) the Caenolestidae can not have been the Polydolopidae's ancestors (so agreement with Odreman's hypothesis); 2) the recognized evolutive grades of the Caenolestidae could represent paralell processes to that of the Polydolopidae although different and independent. Furthermore, the following events are commented: 1) probable extinction of the Polydolopidae by competition with the inmigrant rodents ("pre-Caviomorpha") during the ? Upper Eocene; 2) the unknown reason of extinction of the specialized Palaeothentinae and Abderitinae (Caenolestidae ) ; 3) probable geonemic retraction of the Caenolestinae from theupper Pliocene owing to a competition, by that time, with the Cricetidae rodent inmigrants.